2017
DOI: 10.1016/j.ijsu.2017.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes of pancreaticoduodenectomy in young patients: A case series

Abstract: PD in YA when performed in tertiary centers with good surgical experience is safe. The most common pathological diagnosis in the YA was adenocarcinoma followed by SPT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In a study of pancreaticoduodenectomy in a young population (≤30 years old), Mansfield et al [20] discovered that chronic pancreatitis (6, 27.3%) was the most common postoperative histologic diagnosis, followed by solid pseudopapillary tumors (22.7%) and adenocarcinomas (18.2%). A case series of young adults (less than 35 years) who underwent pancreaticoduodenectomy was described by El Nakeeb et al [1]. The results showed that adenocarcinoma (41.4%) was the most common pathological diagnosis in this cohort, followed by solid pseudopapillary tumors (29.3%).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…In a study of pancreaticoduodenectomy in a young population (≤30 years old), Mansfield et al [20] discovered that chronic pancreatitis (6, 27.3%) was the most common postoperative histologic diagnosis, followed by solid pseudopapillary tumors (22.7%) and adenocarcinomas (18.2%). A case series of young adults (less than 35 years) who underwent pancreaticoduodenectomy was described by El Nakeeb et al [1]. The results showed that adenocarcinoma (41.4%) was the most common pathological diagnosis in this cohort, followed by solid pseudopapillary tumors (29.3%).…”
Section: Discussionmentioning
confidence: 64%
“…The complex and challenging pancreaticoduodenectomy, sometimes called the "Whipple operation" is typically performed on elderly patients with pancreatic cancer and periampullary diseases. Younger patients are rarely given pancreaticoduodenectomy procedures, and the impact of age on surgical and survival outcomes is still unclear [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PE is the committed step in the PD. Although some random studies and meta-analysis have been carried out, there is no evidence or guidelines on how to establish the best PE after PD [2–4, 6–8, 14, 15]. In recent 20 years, despite a significant decline in surgical mortality, the incidence of postoperative complications remains high (about 50%), and the incidence of serious complications of PD is relatively unchanged [16].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, PE technique is the most crucial factor. To prevent pancreatic fistula, different types of surgical techniques to treat the residual end of the pancreas have been proposed [14, 6–8, 14, 15]. However, the efficacy of these techniques remains controversial, and no one is better than other methods [18].…”
Section: Discussionmentioning
confidence: 99%